PTU-125 Positive calprotectin but negative investigations-what next?. (28th May 2012) - Mohammed, N; Smale, S
Abstract : Introduction: Faecal markers are an increasingly established markers of gastrointestinal inflammation. Faecal calprotectin has an important role in differentiating functional from organic disease. 1 2 However a small proportion of patients have an initial abnormal calprotectin and go on to complete normal series of gastrointestinal investigations. We submit this project where in we studied the outcome of those patients who had abnormal faecal calprotectin followed by normal endoscopic/radiological investigations for gastrointestinal diseases, over a period of 3 years. Methods: We identified all 600 patients in our unit who had faecal calprotectins performed between January and June 2007. We then selected all those with abnormal calprotectins (>50 μg/g) whose initial investigations were normal (n=67) and assessed the long term follow-up of these patients. Results: All patients whose initial calprotectin was <225 μg/g had not been found to have any inflammatory or neoplastic gastro-intestinal disease in the following 3 years follow-up. In those whose calprotectin was initially >225 μg/g (n=25) nine were found to have inflammatory bowel disease, 5 were found to have other organic pathology (Clostridium defficile associated Diarrhoea, Coeliac disease, Diverticular disease, Ischaemic colitis) over the subsequent 3 years. In those who had organic disease repeat calprotectin was elevated (3/14). All other patients with an initial calprotectin of >225 μg/g were concluded to have functional disease of whom 8/11 had subsequent faecal calprotectins all of which were normal. Summary: 1. At a calprotectin of <225 μg/g all patients were subsequently concluded to have functional disease. 2. Among those in whom initial calprotectin was >225 μg/g with normal investigation only those with sequentially abnormal calprotectins (mean interval to second calprotectin 6 months, range 60–550 days) had organic disease on follow-up. Conclusion: Negative faecal calprotectin can be a very useful tool to exclude organic pathology. Borderline positive results can be misleading. Serial Calprotectin may hold promise for defining those with post-inflammatory/infective IBS or organic disease. It also reflect response to treatment and aid in disease monitoring, but further longer term study is required. Competing interests: None declared. References: 1. Tibble, et al. Gut 2000;47 :506–13. 2. Limburg, et al . Am J Gastroenterol 2000;95 :2831–7.